An Employment Law Clinic: Developing of Student’s Capacity through Clinical Legal Education in Employment Matters on ASEAN Economic Community Era - Sulistiyono, Tri; Arifin, Ridwan (The Indonesian Journal of International Clinical Legal Education, 2019)
A legal clinic recognized as one of an important program in law school.Legal clinic provides a legal experience to law school students andservices to various clients. Legal clinic typically do pro bono work in aparticular area, providing free legal services to clients. ASEAN EconomicCommunity (AEC) Era become one of challenges for regionalcommunity especially Indonesia on facing and surviving in free tradearea. With high flow of trade activitiesÃ¢â‚¬â€in the context of internationaltrade activitiesÃ¢â‚¬â€the understanding about employment law is neededon only for practitioners but also students as well as law schoolgraduates. The employment law clinic offers legal advice to members ofthe community on a wide array of employment matters. This service iscritical, particularly at a time when the introduction of employment feeshave caused an alarmingly significant drop in claims. This translates toan increase in non-litigated violations of employment law due tofinancial barriers. The paper would examine three main things, first howwas an employment law clinic in law school legal education as a priorbasic understanding to face AEC era, second how an employment lawclinic can be used by students to establish and increase their capacity inthe context of employment matters, and third how this clinic willprovide a legal service in international trade law context as well asconcerning to labor and employment law. The paper focus onemployment law matters, such as illegal deduction of pay case,employment discrimination, unfair dismissal, zero-hour contract, tradeunion freedom in regional Southeast Asia. The paper emphasized thatthe clinic was need to involve some companies and governments aspartner, as well as the practitioners and lawyers.